Incidencia de estrategias pedagógicas de formación en la cultura de paz sobre la promoción de la convivencia escolar (2018)
The purpose of this research was to implement pedagogical strategies for the formation of a culture of peace for the promotion of school coexistence among 5th grade primary school students of the sagrada familia educational institution of san andrés isla; under a mixed research method, and under a research-action approach that involved the analysis of both qualitative and quantitative variables associated with coexistence in the academic environment, we worked with a sample of 40 children of male and female gender. As a result of the research it was found that the strategies designed and implemented had a positive impact on children at the level of coexistence and peace, while children perceive their environment and perceive themselves much more tolerant and willing to mediate; in addition, they also perceived a reduction in conflicts as a product also of the strategies applied